Leucine-Rich Repeat Kinase 2 Gene-Associated Disease: Redefining Genotype-Phenotype Correlation - Wider, Christian (S. Karger AG, 2010)
BACKGROUND: Leucine-rich repeat kinase 2 (LRRK2) has emerged as the most prevalent genetic cause of Parkinson's disease (PD) among Caucasians. Patients carrying an LRRK2 mutation display significant variability of clinical and pathologic phenotypes across and within affected families. METHODS: Herein, we review available clinical and pathologic data on patients with an LRRK2 mutation who have come to autopsy. RESULTS: Thirty-eight patients have been reported who presented clinically with PD; parkinsonism with resistance to levodopa, supranuclear gaze palsy, or autonomic dysfunction; or tremor and dementia. Pathology showed typical PD-type Lewy body disease (LBD) in most patients, whereas in others there was ‘pure’ nigral degeneration (one with TDP-43-positive inclusions), diffuse LBD, or tau-, α-synuclein- or ubiquitin-positive pathology reminiscent of progressive supranuclear gaze palsy, multisystem atrophy, and frontotemporal dementia with ubiquitin-positive inclusions. CONCLUSIONS: Such clinical and pathologic variability suggests Lrrk2 acts upstream from other proteins implicated in neurodegeneration. Specific mutations may be associated with alternative progressive supranuclear gaze palsy-like or ‘pure’ nigral degeneration phenotypes. A different effect on Lrrk2 kinase activity may play a role in such heterogeneity.